Estrutura taxonômica e funcional de comunidades de peixes de riachos no Parque Estadual do Mirador - Maranhão - SILVA, Simone Karla Lima e (2016)
The intrinsic hypothesis of an ecomorphology study predicts that the adaptive characteristics of species under analysis are responses to environmental variations. This work aimed to characterize the taxonomic and functional structure of fish assemblages in streams and then investigate as the environmental characteristics of streams influence these assemblies’ structure patterns. The fish captures point are located in thirteen streams of the Mirador State Park, in a Cerrado area on center-south of Maranhão State. In each stream, we established a stretch of 150m, divided into 11 cross transects distant 10m from each other, where several environmental features registered (e.g. substrate type, average depth, width, water flow and vegetation). Then, we applied dragnets and sieves to capture the specimens used on this research resulting in a collection of 1,120 individuals distributed by 5 orders, 17 families, 30 genera and 32 species. The orders Characiformes and Siluriformes occurred more frequently. The most abundant species were Bryconops sp., which contribute to 27.37% (306 individuals) of the total, Crenicichla menezesi with 11.89% (133 individuals), Astyanax cf. fasciatus with 11.27% (126 individuals), Eigenmannia virescens with 9.03% (101 individuals) and Pimelodella parnahybae with 8.49% (95 individuals). The analysis of the percentage composition related to the frequency of occurrence ranges indicated higher proportion of rare and moderate species, corresponding to a percentage of 34.37% (11 species) and 31.25% (10 species), respectively. From there, the Principal Component Analysis (PCA) applied to the matrix of the morphological attributes of the species found that the size of the eye and relative area of the fins were the attributes that accumulated major fraction of variation. According to redundancy analysis (RDA), the meaningful variables to characterize the vegetation were Canopy Trees Large (DAG), Canopy Trees Small (DAP), Creeping herbs (RE) and Coverage of The Canopy (CDOS) (F = 2 85, p = 0.017). The Functional evenness (FEve) index showed an average values to the majority of streams and the functional divergence (FDiv) index showed higher values for the streams of the Itapecuru River basin, ranging between 0.671 and 0.975. The functional diversity (FDiv) index was applied to compare both, the Itapecuru and Alpercatas watersheds, it not detected significant mean difference (t = 2.16; p = 0.06). The functional diversity shows itself negatively influenced by the presence of creeping herbs. The functional richness tended to show higher values associated with the streams with higher canopy cover, formed by small trees, and slightly lower values, with higher occurrence of large trees and streams with sandy substrate. Functional evenness, in turn, tended to be higher in streams with greater woody understory coverage and higher occurrence of leaves bank. The use of functional attributes might be an effective tool in monitoring biodiversity, to capture key dimensions of ecosystem processes and services, and are easy to assess.